Rate of convergence to the Rosenblatt distribution for additive functionals of stochastic processes with long-range dependence. (2001) - Leonenko, N. N.; Anh, V. V.
Abstract : This paper establishes the rate of convergence (in the uniform Kolmogorov distance) for normalized additive functionals of stochastic processes with long-range dependence to a limiting Rosenblatt distribution.